2018 IEEE Globecom Workshops (GC Wkshps) 2018
DOI: 10.1109/glocomw.2018.8644234
|View full text |Cite
|
Sign up to set email alerts
|

5G Multi-Connectivity with Non-Ideal Backhaul: Distributed vs Cloud-Based Architecture

Abstract: We investigate the throughput performance of multiconnectivity over Heterogeneous Networks (HetNets). Specifically, we examine the effect of non-ideal backhaul on the throughput for two architecture scenarios, namely: i) The distributed HetNet scenario where the multi-connectivity anchor is co-located with the macro cell; ii) the cloud-based HetNet scenario, where the multi-connectivity anchor point is located at a centralized network point. An extensive set of simulations is conducted, followed by an investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The amount of data is computed based on pending data requests, historical data of the throughputs provided, and the buffer status of the SN. The same traffic split algorithm is also used in [24] in which MC is studied in cloud and distributed Heterogeneous Networks (HetNet) architectures.…”
Section: Related Workmentioning
confidence: 99%
“…The amount of data is computed based on pending data requests, historical data of the throughputs provided, and the buffer status of the SN. The same traffic split algorithm is also used in [24] in which MC is studied in cloud and distributed Heterogeneous Networks (HetNet) architectures.…”
Section: Related Workmentioning
confidence: 99%
“…Various architectures have been proposed for implementing multi-connectivity in 5G [18]. Throughput performance of multi-connectivity in distributed and cloud-based heterogeneous network architectures has been compared in [19]. Cloudbased heterogeneous networks have been shown to provide better throughput performance.…”
Section: A Related Literaturementioning
confidence: 99%
“…Network cloudification and programmability allow telecom operators making their networks more scalable, flexible, and agile and to offer innovative and marketoriented services. By centralizing certain functionalities, cloud computing enables on-demand resource sharing and it empowers applications with elasticity and scalability at low cost [16], [17]. In [18], it is shown that the cloud-based heterogeneous access network architecture exceeds the distributed architecture in terms of throughput performance.…”
Section: Related Workmentioning
confidence: 99%